2003
DOI: 10.1086/378778
|View full text |Cite
|
Sign up to set email alerts
|

A Genomewide Screen of 345 Families for Autism-Susceptibility Loci

Abstract: We previously reported a genomewide scan to identify autism-susceptibility loci in 110 multiplex families, showing suggestive evidence (P <.01) for linkage to autism-spectrum disorders (ASD) on chromosomes 5, 8, 16, 19, and X and showing nominal evidence (P <.05) on several additional chromosomes (2, 3, 4, 10, 11, 12, 15, 18, and 20). In this follow-up analysis we have increased the sample size threefold, while holding the study design constant, so that we now report 345 multiplex families, each with at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
238
1
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(251 citation statements)
references
References 52 publications
9
238
1
1
Order By: Relevance
“…Several research groups have performed full genome screens in AD. 40,[119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137] Research groups, study design and main findings of linkage studies that reported positive results are summarized in Table 1 for genome-wide linkage and association studies with a qualitative AD phenotype, and in Table 2 for linkage studies with either a quantitative phenotype, a specific qualitative endophenotype, or other specific linkage models. 122,123,127,130,[138][139][140][141][142][143][144][145][146][147][148] From Table 1, it can be seen that linkage has been found in at least two independent studies in regions 2q, 3q25-27, 3p25, 6q14-21, 7q31-36 and 17q11-21.…”
Section: Linkage Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research groups have performed full genome screens in AD. 40,[119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137] Research groups, study design and main findings of linkage studies that reported positive results are summarized in Table 1 for genome-wide linkage and association studies with a qualitative AD phenotype, and in Table 2 for linkage studies with either a quantitative phenotype, a specific qualitative endophenotype, or other specific linkage models. 122,123,127,130,[138][139][140][141][142][143][144][145][146][147][148] From Table 1, it can be seen that linkage has been found in at least two independent studies in regions 2q, 3q25-27, 3p25, 6q14-21, 7q31-36 and 17q11-21.…”
Section: Linkage Studiesmentioning
confidence: 99%
“…120,125,131,132 A recent heterogeneity-based genome search metaanalysis 150 again supported region 7q22-q32, which reached genomewide significance in studies on strictly defined autism, and revealed two loci of suggestive significance (10p12-q11.1;17p11.2-q12) in studies on AD and the BAP. Nine linkage studies 119,120,123,126,[131][132][133]136,151 were included in this meta-analysis. Between-scan heterogeneity was low for the locus on 7q, but high for the loci on 10p 12-q11.1 and 17p11.…”
Section: Linkage Studiesmentioning
confidence: 99%
“…Notably missing from our genome scan were signals corresponding to those reported by others on chromosome 2 13,16,17,23,45 and chromosome 17. 14,20,24 Gender and linkage analyses Previous work by others suggested that linkage signals on chromosomes 4, 14,20 7, 17 and 17 14,20 were dependent on the gender of the affected individuals in the families. To attempt to replicate these findings, we used the same stratification design, dividing our sample into families with only male affected individuals (MO families; 113 strict, 148 broad), and families with at least one affected female sib (FC families; 56 strict, 74 broad; Table S4).…”
Section: Primary Genome Scanmentioning
confidence: 99%
“…To date, genomewide linkage studies of autism in eight largely nonoverlapping family collections have been published. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] The number of families in these studies ranges from 39 12 to 345 24 families with most kindreds having two affected siblings. While no single region has been unambiguously associated with autism, coincident signals for specific chromosomal regions have been identified in multiple studies.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence is based on the higher ratio of autism recurrence in siblings and a greater concordance in monozygotic twins [Maestrini et al, 2000], although lack of a 100% concordance rate in monozygotic twins also suggests involvement of environmental and other factors in the development or severity of autism [Szatmari, 1999]. Several laboratories around the world are engaged in linkage analysis and positional cloning approaches of genome-wide scans to identify autism susceptibility genes [International Molecular Genetic Study of Autism Consortium IMGSAC, 1998Ashley-Koch et al, 1999;Barrett et al, 1999;Philippe et al, 1999;Buxbaum et al, 2001;Liu et al, 2001;Yonan et al, 2003]. These studies have narrowed a number of chromosomal loci, and strong involvement of genetic loci on chromosomes 2, 7, and 17 has been indicated.…”
Section: Introductionmentioning
confidence: 99%